Practice standard for project estimating (Project Management Institute, 2011)
Consistent with the PMBOK® Guide - Fourth Edition, the Practice Standard for Project Estimating describes the life cycle stages of project estimating. It details the aspects of resources, durations, and costs, and explains the concept of progressive elaboration--continuously refining and improving a plan as a project evolves.